Mao's road to power : revolutionary writings, 1912-1949. Volume X, From the CPC's Strategic Offensive to the establishment of the People's Republic of China, July 1947-October 1949 - Fewsmith, Joseph, 1949-; Hearst, Nancy R. (New York : Routledge, 2023)
The series, Mao's Road to Power, consisting of translations of Mao Zedong's writings from 1912 to 1949, provides abundant documentation in his own words on his life and thought as well as developments in China during the pre-1949 period. This final volume in the series, Volume 10, covers the period from the Chinese Communist Party's Strategic Offense during the Civil War to the Establishment of the People's Republic of China, July 1947 to October 1949.
Keywords: Mao, Zedong, -- 1893-1976.; China -- Politics and government; Communism -- China -- History